2016
DOI: 10.5937/fmet1604422s
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of FEM and rapid prototyping in maxillofacial surgery

Abstract: This paper investigates the opportunity of implementing FE simulations and rapid prototyping tecniques on titanium implant in maxillofacial surgery case based on osteotomy. Maxilla region was recorded by Cone Beam CT with high resolution and optimal radiation. Then, it followed the medical image reconstruction into 3D voxelized model. This model was converted both, to stl surface model for rapid prototyping, CAD modeling and FE mesh for simulation purposes with keeping good volume and dimensional consistency. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 5 publications
0
9
0
1
Order By: Relevance
“…[42] Decomposable porous scaffold structures [38] Dental repairs, scaffold for organ printing and tissue engineering [43] Polycaprolactone/hydroxyapatite artificial bones to imitate goat femur [44] Maxillofacial surgery using FDM and poly-jet printing along with finite element analysis (FEA) Simulation and modelling. [45] Printing capsules in the pharmaceutical business.…”
Section: Applications Referencementioning
confidence: 99%
“…[42] Decomposable porous scaffold structures [38] Dental repairs, scaffold for organ printing and tissue engineering [43] Polycaprolactone/hydroxyapatite artificial bones to imitate goat femur [44] Maxillofacial surgery using FDM and poly-jet printing along with finite element analysis (FEA) Simulation and modelling. [45] Printing capsules in the pharmaceutical business.…”
Section: Applications Referencementioning
confidence: 99%
“…The impact of implant inclination on the surrounding structure has been frequently researched in the overdenture settings (Behnaz et al 2015, Gul and Suca 2014, Markarian and Ueda 2007, Cağlar et al 2006, Almeida et al 2013, Hong et al 2012, Lan et al 2010, Sljivic et al 2016, Takahashi, Shimamura and Sakurai 2010, Ueda et al 2004, Naini et al 2011, rather than in an isolated environment, as explained in Watanabe et al (2003). The intention in this study was to focus on the simpler loading conditions and to eliminate other systematical factors which arise due to the system complexity.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that this method provided good results in combination with dental implants and acrylate blocks [33][34][35]. This experimental study also employs consumer grade FDM 3D printing technique which is already used in dental application [36,37].…”
Section: Introductionmentioning
confidence: 95%